Conductivity and Chemiresistive H2S Gas Sensitivity of Graphene (75 wt%)/ Cu (25 wt%) Composite Thin Film - Omoniyi, Francis; Aderemi B. , Alabi; Mufutau A. , Salawu; Olayinka A. , Babalola (Journal of Science and Technology, 2024)
This paper studies the conductivity and chemiresistive H2S gas sensitivity of graphene(75wt%)-Cu(25wt%) composite thin film, using self-made chamber and common laboratory apparatus. The method adopted involves mixture of 2 drops of ethanol with the synthesized composite and prepared on a glass substrate by tape casting method. Two small copper metal sheets were used as electrodes for clipping of crocodile which were also connected to digital meter for resistance readings and its changes. The X-ray Diffraction (XRD) shows that annealing temperature reduced the crystallite sizes. The Fourier Transform Infrared Radiation (FTIR) spectra show the functional groups present to be transition metal carbonyls or aromatic combination bands, terminal alkyne (monosubstituted), isothiocyanate and that between 2300 and 2400 cm-1 indicates N=C=S functional group and evidence of CO2 interaction with external surface of the material or intercalating in the interlayer of the host material Also, increase in the conductivity was observed due to decrease in resistivity. The response/sensitivity peak of the sensor to hydrogen sulfide was seen to rise proportionally as temperature rose with percentage 3.97% for as grown, annealed at 200°C is at 12.98% while the annealed at 400°C is at 27.34%.